DIGITAL LITERACY PRACTICES OF ENGLISH TEACHER PROFESSIONAL EDUCATION PROGRAM (PPG) STUDENTS IN PREPARING ONLINE KNOWLEDGE TEST (UP) - Lestari Budianto; Akhmad Fauzi; Muhammad Badrul Mutammam (IKIP Siliwangi, 2023)
Since the outbreak of the Covid-19, Teacher Professional Education Program (PPG) provided by the Indonesian government to improve the quality of Indonesian education became online. The students of PPG should pass the final exam namely Knowledge Test (UP) to get the certificate. There were two kinds of the online exam system (visiting campus and from home). This research investigates the PPG students’ digital literacy practices in preparing an online knowledge test (UP) both from campuses and homes as well. This research used mix method that the data gained from questionnaires, observation, semi-structured interviews, and documentation. The result of this research showed that the top digital tools used by the participants were laptop, WhatsApp, Google, Zoom, Google Meet, Brainly.com, YouTube, Offline dictionary, and Google drive. This research also revealed the challenges the participants had to deal with. Moreover, the participants applied strategies to overcome the challenges. This research was limited to the investigation of English students’ digital literacy practices of the Teacher Professional Education Program (PPG) in preparing online knowledge test (UP). It is suggested to investigate the participants’ perceptions towards the system of the test or students from different disciplines. Keywords: Digital Literacy Practices; PPG; Online